Bowhead Whale (Balaena mysticetus) Feeding near Point Barrow, Alaska, During the 1985 Spring Migration - Carroll, Geoffry M.; George, John C.; Lowry, Lloyd F.; Coyle, Kenneth O. (ARCTIC, 1987)
Examination of stomach contents and behavioral observations showed conclusively that bowhead whales were feeding in the Point Barrow area during the spring of 1985. All three bowheads harvested near the village of Barrow had over five litres of pelagic zooplankton (calanoid copepods and euphausiids) in their stomachs. Over 60 whales were observed during the period 26 May through 6 June diving repeatedly under the landfast ice and feeding in an area 11.2 km southwest of Point Barrow. Observers recorded times for dive, surfacing and respiration intervals for these whales. The recorded times were significantly different from those of bowhead whales migrating past Point Barrow in the spring and from bowheads, whose major activity was feeding, recorded in the Canadian Beaufort Sea during the summer and fall.Key words: Balaena mysticetus, Point Barrow, feeding, bowhead whale, behavior, copepod, euphausiid, respiration, spring Un examen du contenu stomacal de baleines franches et des observations de leur comportement ont montré sans aucun doute qu’elles se nourrissaient dans la zone de Point Barrow pendant le printemps de1985. Les trois baleines franches pêchées près du village de Barrow avaient toutes dans l’estomac plus de cinq litres de zooplancton pélagique (copépodes calanoïdes et euphausiacés). Pendant la période allant du 26 mai au 6 juin, on a observé plus de 60 baleines qui plongeaient de façon répétée sous la banquise côtière pour se nourrir dans une zone située à 11,2 km au sud-ouest de Point Barrow. Les observateurs ont noté le moment de la plongée et celui du retour à la surface, et l’intervalle entre les souffles des baleines. Les durées enregistrées étaient nettement différentes de celles mesurées pour des baleines franches qui passaient à Point Barrow pendant leur migration au printemps, et de celles enregistrées dans la mer de Beaufort canadienne en été et en automne pour des baleines franches dont l’activité principale était de se nourrir.Mots clés: Balaena mysticetus, Point Barrow, se nourrir, ...